THE SECRETS ENCODED IN THE DRAFT GENOME OF Lentzea sp. STRAIN BCCO 10_0061 ISOLATED FROM RECLAIMED MINE HEAPS - Keller, Moritz (Jihočeská univerzita, 2023)
Many Actinobacteria including Lentzea have been found to produce medically viable compounds like antibiotics and antitumor agents. This thesis deals with genome sequencing of Lentzea sp. BCCO 10_0061, assembly, annotation and evaluation of the potential for secondary metabolite production, as well as phylogenetic classification and creation of a metabolic profile.
THE SECRETS ENCODED IN THE DRAFT GENOME OF Lentzea sp. STRAIN BCCO 10_0061 ISOLATED FROM RECLAIMED MINE HEAPS
Keywords: Actinobacteria; Lentzea; genome assembly; iso-migrastatin; nystatin A1; biosynthetic gene clusters; Actinobacteria; Lentzea; genome assembly; iso-migrastatin; nystatin A1; biosynthetic gene clusters